Vitrification and Rewarming of Magnetic Nanoparticle‐Loaded Rat Hearts. Issue 3 (1st October 2021) - Gao, Zhe; Namsrai, Baterdene; Han, Zonghu; Joshi, Purva; Rao, Joseph Sushil; Ravikumar, Vasanth; Sharma, Anirudh; Ring, Hattie L.; Idiyatullin, Djaudat; Magnuson, Elliott C.; Iaizzo, Paul A.; Tolkacheva, Elena G.; et al.
Abstract: To extend the preservation of donor hearts beyond the current 4–6 h, this paper explores heart cryopreservation by vitrification—cryogenic storage in a glass‐like state. While organ vitrification is made possible by using cryoprotective agents (CPA) that inhibit ice during cooling, failure occurs during convective rewarming due to slow and non‐uniform rewarming which causes ice crystallization and/or cracking. Here an alternative, "nanowarming", which uses silica‐coated iron oxide nanoparticles (sIONPs) perfusion loaded through the vasculature is explored, that allows a radiofrequency coil to rewarm the organ quickly and uniformly to avoid convective failures. Nanowarming has been applied to cells and tissues, and a proof of principle study suggests it is possible in the heart, but proper physical and biological characterization especially in organs is still lacking. Here, using a rat heart model, controlled machine perfusion loading and unloading of CPA and sIONPs, cooling to a vitrified state, and fast and uniform nanowarming without crystallization or cracking is demonstrated. Further, nanowarmed hearts maintain histologic appearance and endothelial integrity superior to convective rewarming and indistinguishable from CPA load/unload control hearts while showing some promising organ‐level (electrical) functional activity. This work demonstrates physically successful heart vitrification and nanowarming and that biological outcomes can be expected to improve by reducing or eliminating CPA toxicity during loading and unloading. Abstract : Heart cryopreservation by vitrification and nanowarming has immense promise for transforming transplant medicine. Here, comprehensive validation of the approach, including machine perfusion loading/unloading of cryoprotective agents (CPA) and magnetic nanoparticles, cooling to a vitrified state, and fast and uniform radiofrequency rewarming without crystallization or cracking is shown. Nanowarmed hearts maintain histologic appearance and endothelial integrity similar to CPA load/unload controls with some organ‐level (electrical) functional activity.